The DART general equilibrium model: A technical description - Katrin Springer (Kiel Institute of World Economics (IfW); ZBW – Leibniz Information Centre for Economics, 1998)
This paper provides a technical description of the Dynamic Applied Regional Trade (DART) General Equilibrium Model. The DART model is a recursive dynamic, multi-region, multi-sector computable general equilibrium model. All regions are fully specified and linked by bilateral trade flows. The DART model can be used to project economic activities, energy use and trade flows for each of the specified regions to simulate various trade policy as well as environmental policy scenarios, and to analyze the allocational and distributional impacts of these policies.
Keywords: C68; D1; D21; O41; 330; Computable General Equilibrium model; Multi-Sector Recursive Dynamic Model; Climate Change; International Trade